The Evolution of Digital Stories: Bibliometric Analysis - Bulut, Aydın (Kastamonu Egitim Dergisi, 2025)
Purpose: The present study has been designed to analyse the extant literature on 'digital stories' from a bibliometric perspective, with a view to creating a bibliometric map of studies investigating their use in educational environments. Design/Methodology/Approach: In this study, a range of analytical methods were employed to analyse studies on 'digital stories'. These methods included publication co-citation analysis, author co-citation analysis and word frequency analysis.Descriptive data on the distribution of studies in the field by country, institution and time were obtained from the Web of Science (WoS) database. The analysis was performed using 'R version 12.0 software' and various libraries including 'bibliometrix', 'wordcloud' and 'ggplot2'. Findings: A bibliometric analysis of 597 articles on 'digital stories' published in the WoS database since 2005 was conducted, and the results obtained are presented in all aspects. Between 2005 and 2025, 597 articles from 270 sources on 'digital stories' were published, with an average of 29.85 articles published per year. The average number of citations per document for these articles is 15.91, and the total number of references is 19,958. The number of Keywords Plus for these articles is 556, and the number of Author's Keywords is 1,633. The number of authors of single-author documents is 156, and the number of authors of multi-author documents is 1,166. The number of single-authored documents is 168, while the number of multi-authored articles is 429. The average number of co-authors per article is 2.53, and the international co-authorship rate is 10.22%. Highlights: The findings of this study demonstrate the considerable potential of digital storytelling to align with contemporary educational approaches, its interdisciplinary applicability, and its capacity to promote student-centred teaching methodologies. It was revealed that digital storytelling contributes to the acquisition of 21st-century skills, especially in terms of increasing student engagement, personalising learning, encouraging creative thinking, and developing digital literacy skills.